Saving energy at home: Exploring the role of behavior regulation and habit. (18th June 2021) - Webb, Dave; Soutar, Geoffrey N.; Gagné, Marylène; Mazzarol, Tim; Boeing, Alexandra
Abstract: Global demand for energy, environmental concerns over power generation emissions, and rising household energy costs have heightened interest in exploring ways to reduce energy consumption. Numerous approaches have been adopted, including those that build on the important recognition of consumer intentions as a predictor of behavior. However, the literature suggests intentions only moderately explain behavior. Thus, there is a case for further research to explore how the intention to behavior relationship can be strengthened. In response, this study contributes to a better understanding of how to reduce household energy consumption, by investigating the direct, and moderating effects integrated regulation and external regulation, as well as habit, have on the relationship between intention and behavior. The study draws on a large sample of household energy consumers who completed online surveys two months apart. The findings reveal a strong indirect relationship between integrated regulation and behavior through intention, and a significant, direct, and negative relationship between external regulation and behavior. While external regulation moderated the positive relationship between intentions and behavior, the moderating effects of integrated regulation and habit were not significant. Further, a direct effect for habit on behavior was found. These findings suggest regulation types play different roles in affecting consumer intentions and behavior, and support the importance of habit as a predictor of energy consumption.